Electro-Optical Characteristics of Polymer Dispersed Liquid Crystal Doped with MgO Nanoparticles - Yuzhen Zhao; Jinqian Li; Yang Yu; Yang Zhao; Zhun Guo; Ruijuan Yao; Jianjing Gao; Yongming Zhang; Dong Wang (Molecules, 2022)
In this paper, inorganic oxide MgO nanoparticles-doped polymer dispersed liquid crystal (PDLC) films were made from a mixture of the prepolymer, SLC1717 liquid crystal, and MgO nanoparticles by the polymerization induced phase separation (PIPS) process. To observe the effect of MgO concentration, PDLC was dispersed with 0.2, 0.4, 0.6, and 0.8 wt.% MgO. Electro-optical properties of the films have been investigated using LCD parameter meter and Scanning Electron Microscope (SEM) at room temperature. It is established that MgO nanoparticles affect the microstructure of PDLC films significantly because of the formed agglomerates of MgO nanoparticles. Results show an improvement in the electro-optical properties and a decrease in the driving voltage for doped systems with MgO nanoparticles. When the doping amount of MgO is 0.8 wt.%, the threshold voltage (Vth) is reduced to about 7.5 V. Therefore, MgO-doped PDLC is expected to become an excellent choice in the field of energy-saving.